Prevalence and Progression of Ametropias in Medical Students - Gustavo Costa Santos; Rafael Cunha de Almeida; Willany Veloso Reinaldo; Fernando Rocha Oliveira; Shaun Schofield; Roberto Conde Santos; Glaucia Luciano da Veiga; Fernando Luiz Affonso Fonseca; Vagner Loduca Lima; Renato Galão Cerquinho Leça (International Journal of Medical Students, 2021)
Background: Uncorrected refractive errors (Myopia, Hyperopia and Astigmatism) are one of the main causes of poor vision, attributing to 43% of vision deficiencies. Myopia is the most common visual disorder in the world and can progress up until the age of 20-25, when many people are in university. The etiological factors that cause myopia are still unclear and deserve to be studied. Our aim was to identify the prevalence of ametropias and self-perception of ophthalmic health in medical students at the Centro Universitário Saúde ABC/FMABC.